Impact of morphine use on mortality in STEMI patients treated with primary PCI – results from a new registry. (14th October 2021) - Szabo, D; Szabo, A; Edes, I F; Becker, D; Merkely, B; Hizoh, I
Abstract: Background: Opioids decrease the effect of P2Y12 receptor inhibitors in vitro and observational reports suggest that morphine use may be associated with larger infarct size. Our research group showed previously, using a prospective single-centre registry, that periprocedural morphine use may have no impact on long-term mortality in STEMI patients treated with primary PCI and clopidogrel. Purpose: We aimed to study this in vitro interaction on clinical outcomes in patients who were predominantly treated with the novel P2Y12 inhibitors prasugrel or ticagrelor, according to the current guidelines. Methods: From May 2020 through February 2021, we collected demographic, anamnestic, procedural and laboratory data of 297 consecutive STEMI cases who were treated with primary PCI at our tertiary centre. Of them 126 patients (42.4%) received IV morphine during the periprocedural period. Outcome measure was time to all-cause mortality. The median follow-up time was 147 days (IQR 71–242 days), with 39 events. To adjust for confounding, a 1:1 propensity score-matching analysis (PSM) was performed using 186 cases. Absolute difference in survival was analysed using Kaplan-Meier survival curves and the logrank test, whereas the relative change was assessed by univariable Cox regression. Results: An adequate balance on baseline covariates was achieved by the propensity score-matching. Kaplan-Meier analysis showed no statistically significant difference in all-cause mortality of the treatment groups neither in the original nor in the propensity score-matched population (p=0.220 and 0.762 respectively). In the matched population we found no difference in survival as the HR (Morphine/No Morphine) was 0.88 (95% confidence interval [CI]: 0.39–2.00), p=0.76. Conclusion: Our preliminary data suggest that morphine may have no impact on mortality in STEMI patients treated with primary PCI and medical therapy according to the current guidelines including novel P2Y12 antagonists. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The research was supported by the Ministry of Innovation and Technology NRDI Office within the framework of the Artificial Intelligence National Laboratory Program.